Earnings and Labour Market Volatility in Britain - Lorenzo Cappellari; Stephen P. Jenkins (Institute for the Study of Labor (IZA), 2013)
We provide new evidence about earnings and labour market volatility in Britain over the period 1992-2008, and for women as well as men. (Most research about volatility refers to earnings volatility for US men.) We show that earnings volatility declined slightly for both men and women over the period but the changes are not statistically significant. When we look at labour market volatility, i.e. including in the calculations individuals with zero earnings as well as employees with positive earnings, there is a marked and statistically significant decline for both women and men, with the fall greater for men. Using variance decompositions, we show that the fall in labour market volatility is largely accounted for by changes in employment attachment rates. Labour market volatility trends in Britain, and what contributes to them, differ from their US counterparts in several respects.
Keywords: J31; 330; labour market volatility; earnings volatility; earnings instability; BHPS